Antifungal Properties of Hydrazine-Based Compounds against Candida albicans - Louis Camaioni; Dylan Lambert; Boualem Sendid; Muriel Billamboz; Samir Jawhara (Antibiotics, 2023)
Candida albicans, an opportunistic yeast, is the most common cause of fungal infection. In the past decade, there has been an increase in C. albicans resistance to existing antifungal drugs, which has necessitated the development of new antifungal agents. In the present study, screening 60 compounds from the JUNIA chemical library enabled us to explore an additional 11 hybrid compounds that contain pyrrolidinone rings and hydrazine moieties for their potential antifungal activities. This chemical series was identified with fair to excellent antifungal activities. Among this series, three molecules (Hyd.H, Hyd.OCH3, and Hyd.Cl) significantly reduced C. albicans viability, with rapid fungicidal activity. In addition, these three compounds exhibited significant antifungal activity against clinically isolated fluconazole- or caspofungin-resistant C. albicans strains. Hyd.H, Hyd.OCH3, and Hyd.Cl did not show any cytotoxicity against human cancer cell lines up to a concentration of 50 µg/mL and decreased Candida biofilm formation, with a significant reduction of 60% biofilm formation with Hyd.OCH3. In an infection model of Caenorhabditis elegans with C. albicans, hydrazine-based compounds significantly reduced nematode mortality. Overall, fungicidal activity was observed for Hyd.H, Hyd.OCH3, and Hyd.Cl against C. albicans, and these compounds protected C. elegans from C. albicans infection.